Hepatitis B/C virus co-infection in Iran: A seroepidemiological study - Shahryar SEMNANI; Gholamreza ROSHANDEL; Nafiseh ABDOLAHI; Sima BESHARAT; Abbas-Ali KESHTKAR; Hamidreza JOSHAGHANI; Abdolvahab MORADI; Khodaberdi KALAVI; Ali JABBARI; Mohammad Javad KABIR; et al. (Turkish Journal of Gastroenterology, 2019)
-